(untitled) - Collins, Heidi (Amsterdam, 2006)
Collaboration is critical to knowledge worker performance. The authors go well beyond the previous injunctions to "play nice together," and identify ways to improve processes and make money
Keywords: Strategic planning,Organizational change,Management,Quản lý,Thay đổi tổ chức,Lập kế hoạch chiến lược